Improvements in malaria testing and treatment after a national community health worker program in rural Liberia - Jeffrey W. Rozelle; Jerome Korvah; Olasford Wiah; John Kraemer; Lisa R. Hirschhorn; Matt R. Price; Marion Subah; Lisha McCormick; Brittney Varpilah; Rajesh Panjabi (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Progress in reducing malaria incidence and deaths has stalled, in part due to limited access to quality malaria testing and treatment amongst rural populations. This time-series analysis aims to describe changes in rural malaria diagnosis and treatment before and during the rollout of Liberia's National Community Health Assistant (CHA) program. It also explores how malaria service delivery changed during the COVID-19 epidemic. # Methods Malaria diagnosis and treatment data from 315 rural health facility catchments supported by Liberia's National CHA Program were collected from Liberia's Health Management Information System and analyzed. Trends in malaria service delivery coverage and quality were assessed between January 2011 and December 2020. # Results By 2020, four years after the program's introduction, Liberia's Community Health Assistants diagnosed 50% of rapid diagnostic test (RDT) or microscopy-confirmed malaria cases and carried out 51% of malaria treatments amongst children under age five in rural areas where CHAs were present. Furthermore, the percentage of malaria diagnoses that were confirmed by microscopy or RDT increased from 71% prior to the program to 95% in 2020. These results were effectively sustained in rural and remote communities during COVID-19 in 2020. # Conclusions The introduction of Liberia's CHA program was associated with improvements in the quality of malaria diagnoses and contributed to treating a significant share of the malaria burden amongst children under age five in remote rural communities across Liberia, and these improvements were sustained during COVID-19. Investments made in rural community health systems can be leveraged by policy makers to strengthen malaria diagnosis, treatment and control, especially in the age of COVID-19.